Microwave Photonics, 2007 Interntional Topical Meeting On 2007
DOI: 10.1109/mwp.2007.4378132
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 2 THz Span Optical Comb in a Tunable Fiber Ring Based Optical Frequency Comb Generator

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…Later, frequency domain analysis was provided to understand the effects of fiber dispersion, the non-flat gain profiles, and the RF mismatch. OFCs having a 1 THz (100 lines, 6 dB flatness) and 2 THz (200 lines, 10 dB flatness) spectral bandwidth were reported in [167], [168]. The authors also demonstrated frequency spacing tuning from 6 GHz to 12.5 GHz in 12.5 MHz steps, while maintaining the spectral profile.…”
Section: A Electro-optic Optical Frequency Comb Generatorsmentioning
confidence: 96%
“…Later, frequency domain analysis was provided to understand the effects of fiber dispersion, the non-flat gain profiles, and the RF mismatch. OFCs having a 1 THz (100 lines, 6 dB flatness) and 2 THz (200 lines, 10 dB flatness) spectral bandwidth were reported in [167], [168]. The authors also demonstrated frequency spacing tuning from 6 GHz to 12.5 GHz in 12.5 MHz steps, while maintaining the spectral profile.…”
Section: A Electro-optic Optical Frequency Comb Generatorsmentioning
confidence: 96%
“…Experimentalmente se ha demostrado [4], [15], que la generación de peines basados en anillo de fibra óptica tienen gran ancho de banda (> 1THz) y pueden ser sintonizables en cuanto al espaciamiento entre modos en pasos de MHz [17], insertando en el interior del anillo una línea de retardo óptico ajustable (delay line) que permite una fina sintonización de la longitud de la cavidad. Sin embargo, sus desventajas son que se trata de estructuras discretas de grandes dimensiones, la longitud de la fibra que se necesita es larga (decenas de metros [6]) y las variaciones térmicas existentes que influyen en los dispositivos.…”
Section: B Peines De Frecuencias óPticas Mediante Moduladores En Anunclassified
“…En la tabla 1 se presentan los parámetros de peines ópticos medidos en diversas estructuras con moduladores en anillo recirculante. Podemos observar que para el caso de anillos con fibra óptica se logran grandes anchos de banda (16 nm @-10 dB [17].…”
Section: Output Inputunclassified
“…Several techniques have been developed over recent years and compact sources are now available [13][14][15][16], either fiber or semiconductor based. For example, a system based on the fiber recirculating loop can offer over a hundred highly coherent lines, which are equally spaced in frequency, as determined by an external synthesizer.…”
Section: Current Component Performancementioning
confidence: 99%
“…The best performing OFCG of that type, as proposed in [17], should offer up to 10 THz in span, using parametric methods, with several mW of total output power, while short pulse mode locked lasers have achieved similar performances. Compact sources have achieved up to 2 THz span [13] with similar power. Current performance is therefore close to what will be needed for the system, as only a few mW will be required to lock the slave lasers and a span of 5THz will be sufficient to access most applications.…”
Section: Current Component Performancementioning
confidence: 99%